Results of a UK-wide vignette study with occupational therapists to explore cognitive screening post stroke. (2nd July 2020) - Geraghty, Jennifer; Ablewhite, Joanne; das Nair, Roshan; Lincoln, Nadina; Kontou, Eirini; Roffe, Jack; Lannin, Natasha; Drummond, Avril
Abstract : Background/Aims: There is a paucity of evidence in the UK regarding cognitive screening performed by occupational therapists and whether, and how, cognitive impairments are identified and assessed. The aim of this study was to identify current occupational therapy practice for the assessment of cognitive problems in patients following stroke. Methods: Occupational therapists were invited to complete an online vignette study. Participants were asked to: identify any presenting cognitive problems; decide whether to complete cognitive assessments; and list any assessments they would use. Data were analysed using descriptive analysis. Results: A total of 53 occupational therapists from across the UK participated. Participants identified key cognitive issues, but some problems, such as apraxia and attention, were overlooked. A large number of potential assessments were suggested, the most common being the Montreal Cognitive Assessment and Oxford Cognitive Screen. Conclusions: The variation found in occupational therapists' recognition and assessment of cognitive problems has the potential to impact on management and rehabilitation in stroke services, survivor outcomes, education and research.